FSKTM Rooms Reservation System / Voon Sheau Yun - Voon, Sheau Yun (2001)
For the past few years, the room reservation system at Faculty of Computer Science and Information Technology (FSKTM), University Malaya, has been carried out manually. In order to keep up with fast growing technology, it is worthwhile to develop a computerized room reservation system. With this automated system, the faculty will be able to increase efficiency in management operations and time saving. Following from that, I have decided to develop this FSKTM Rooms Reservation System, or RRS as my final year project. FSKTM Rooms Reservation System is a combination of internet-based system and client-server application system. This system is developed with the objectives on utilizing the state-of-art form of information dissemination in the Internet in order to provide easy and convenient room reservation service to the staff of FSKTM. This will also eliminate the workloads of manual checking by administrators. This FSKTM Rooms Reservation System is developed by using Active Server Pages (ASP) technologies, utilizing Microsoft Access 2000 database. As this system is developed with the intention of transforming the old manual system to a computerized and web-based system, it is believed that this system would be beneficial to everyone inclusive of the lecturers, technical staffs and administration staffs in the future.